Optical coherence tomography and visual acuity: photoreceptor loss - Salam, Adzura; Wolf-Schnurrbusch, Ute Ellen Kathrin; Wolf, Sebastian (Springer, 2012)
SD-OCT has improved the visualization of intraretinal morphologic features quantitatively and qualitatively. SD-OCT allows the retinal physician to evaluate the integrity of each retinal layer such as the external limiting membrane (ELM) and the junction between the inner and outer segments (IS/OS junction) of the photoreceptors The presence and integrity of the external limiting membrane (ELM), the photoreceptor inner segment(IS), the outer segment(OS), and the retinal pigment epithelium (RPE) appears to be a good prognostic feature for visual improvement after treatment for various macular diseases.